Real-World Costs of Azacitidine Treatment in Patients With Higher-Risk Myelodysplastic Syndromes/Low Blast–Count Acute Myeloid Leukemia. Issue 4 (April 2021) - Mozessohn, Lee; Cheung, Matthew C.; Mittmann, Nicole; Earle, Craig C.; Liu, Ning; Buckstein, Rena
Abstract : PURPOSE: Azacitidine (AZA) is a standard of care for higher-risk myelodysplastic syndrome (MDS)/low blast–count acute myeloid leukemia (AML). Despite this, there is a paucity of data on the real-world health care resource utilization costs of AZA in this population. METHODS: We linked the Ontario AZA MDS registry—higher-risk MDS/low blast–count AML—to population-based health system administrative databases. Patients were observed for 24 months after first AZA and censored at the earliest of 90 days after last AZA, date of death, time of AML induction/stem-cell transplantation, or March 31, 2016. Costs (2015 Canadian dollars) were expressed as standardized mean and median 28-day costs. Univariable quantile regression was used to explore the association of baseline patient and disease characteristics and median cost. Multivariable quantile regression was used to explore predictors of median costs. RESULTS: Among 877 patients in the registry, mean standardized 28-day cost per patient was 17, 638 (median, 15, 272; interquartile range [IQR], 11, 869-19, 580) and 13, 450 (median, 11, 043; IQR, 7, 981-14, 882) excluding the cost of AZA. Major nondrug drivers of cost were cancer clinic visits and inpatient care (mean standardized 28-day cost, 4, 631; median, 1, 558; IQR, 238-4, 961). Transfusion dependence at AZA initiation ( P = .001) and greater comorbid disease burden ( P = .009) were independently associated with increased cost. CONCLUSION: Our cohort of patients with uniformly higher-risk MDS/low blast–count AML treated with AZA demonstrates substantial costs of care above and beyond the cost of AZA alone. These results provide insight into the costs of AZA in the real world with implications for resource allocation.